On pairwise almost Regular-Lindel of spaces. - Kilicman, Adem; Salleh, Zabidin (Japanese Association of Mathematical Sciences, 2009)
In this work, we introduce and study the pairwise almost regular-Lindel¨of bitopological spaces, their subspaces and subsets, and investigate some of their characterizations. We also show that a pairwise almost regular-Lindel¨of property is not a hereditary property.